A new species of Bolitoglossa (Caudata: Plethodontidae) of the Bolitoglossa franklini group from an isolated cloud forest in northern Guatemala - Dahinten-Bailey, Hellen; Serrano, Marcelo J.; Alonso-Ascencio, Margarita; Cruz-Font, Jose J.; Rosito-Prado, Isabella; Ruiz-Villanueva, Kennedy J. A.; Vásquez-Almazan, Carlos; Ariano-Sánchez, Daniel (Zootaxa, 2021)
We describe Bolitoglossa qeqom sp. nov. from an isolated cloud forest in Cerro Guachmalén, Alta Verapaz, Guatemala, based on multiple lines of evidence (morphological, molecular, and biogeographic data). This region comprises a mountain ridge without previous herpetological surveys. The new species is a large salamander with uniform purplish-black coloration and is distinguished by having relatively long legs with only one costal groove between adpressed limbs, numerous maxillary teeth, few vomerine teeth, only one phalange free of webbing in digit III of feet, and a relatively short tail. It is geographically closest to its sister clade of B. lincolni + B. franklini and the xeric Chixoy river canyon appears to be the major biogeographic barrier that isolated the new taxon. The cloud forest inhabited by this species has undergone severe habitat destruction in the region and land conservation actions are urgent.